Inborn errors of metabolism: a clinical overview - Martins, Ana Maria (São Paulo Medical Journal, 1999)
CONTEXT: Inborn errors of metabolism cause hereditary metabolic diseases (HMD) and classically they result from the lack of activity of one or more specific enzymes or defects in the transportation of proteins. OBJECTIVES: A clinical review of inborn errors of metabolism (IEM) to give a practical approach to the physician with figures and tables to help in understanding the more common groups of these disorders. DATA SOURCE: A systematic review of the clinical and biochemical basis of IEM in the literature, especially considering the last ten years and a classic textbook (Scriver CR et al, 1995). SELECTION OF STUDIES: A selection of 108 references about IEM by experts in the subject was made. Clinical cases are presented with the peculiar symptoms of various diseases. DATA SYNTHESIS: IEM are frequently misdiagnosed because the general practitioner, or pediatrician in the neonatal or intensive care units, does not think about this diagnosis until the more common cause have been ruled out. This review includes inheritance patterns and clinical and laboratory findings of the more common IEM diseases within a clinical classification that give a general idea about these disorders. A summary of treatment types for metabolic inherited diseases is given. CONCLUSIONS: IEM are not rare diseases, unlike previous thinking about them, and IEM patients form part of the clientele in emergency rooms at general hospitals and in intensive care units. They are also to be found in neurological, pediatric, obstetrics, surgical and psychiatric clinics seeking diagnoses, prognoses and therapeutic or supportive treatment.